Rancangan Teknis Penambangan Bijih Nikel pada Daerah Blok C PT XYZ Desa Boenaga, Kecamatan Lasolo, Kabupaten Konawe Utara, Provinsi Sulawesi Tenggara - Adit Kurniawan; Dudi Nasrudin; Rully Nurhasan (Jurnal Riset Teknik Pertambangan, 2021)
Abstract. Planning and design are important things in mining activities because they are used as technical requirements and technical sequences for the purposes and objectives of mining activities. The purpose of this research activity is to determine the technical design of nickel ore mining activities at the mining stage and production scheduling obtained based on exploration data and in accordance with mining design parameters such as Cut off Grade, Stripping Ratio and Geometry Grades and mining roads. Before the design is carried out, it is necessary to know the sediment distribution model, and first. Sediment modeling and estimation of nickel ore resources used is by making block models using the inverse distance method to describe the distribution of the levels. The result of calculations using the block model is that the measured resource is 142,400 tons with an average Ni content of 1.8%. The mine design was made by based on the Cut Off Grade value used, average Ni 1.6% and the Stripping Ratio value of 6,7 tonnes of waste / tonnes of ore with a geometric level with a height of 6 m and a slope of 40o. The road geometry used is a straight road width of 9 m with a cross slope of 1.71o and a curved road width of 17 m. From this limitation, it is obtained a mining limit of 8,3 hectares with the mining method to be used, namely the side cast method. Based on the mine opening design, the production of mined reserves is 137,000 tons of nickel with an average grade of 1,86% and 834,118 tons of waste to be peeled, resulting in a stripping ratio of 6.49 tons of waste / ton of ore with a company target of 40,000 tons / month, so mining will planned for 3 months. Abstrak. Perencanaan dan perancangan merupakan hal penting dalam kegiatan penambangan karena dijadikan sebagai persyaratan teknik serta urutan teknis untuk pencapaian tujuan dan sasaran kegiatan penambangan. Tujuan dari kegiatan penelitian ini yaitu untuk mengetahui rancangan teknis kegiatan penambangan bijih nikel terutama tahapan penambangan dan penjadwalan produksi yang diperoleh berdasarkan data hasil eksplorasi dan sesuai dengan parameter rancangan penambangan seperti Cut off Grade, Stripping Ratio serta Geometri Jenjang dan jalan tambang. Sebelum dilakukan perancangan maka perlu diketahui model sebaran endapan, kadar dan sumberdaya. Pemodelan endapan dan penaksiran sumberdaya bijih nikel yang digunakan yaitu dengan pembuatan blok model dengan menggunakan metode inverse distance untuk menggambarkan sebaran kadarnya. Hasil perhitungan dengan menggunakan blok model yaitu diperoleh sumberdaya terukur sebesar 142,400 ton dengan kadar rata-rata Ni 1,8%. Rancangan bukaan tambang dibuat berdasarkan nilai Cut Off Grade yang digunakan yaitu Ni rata-rata 1.6 % dan nilai Stripping Ratio sebesar 6,7 ton waste/ton ore dengan geometri jenjang dengan tinggi 6 m dan kemiringan 40°. Geometri jalan yang digunakan yaitu lebar jalan lurus 9 m dengan nilai cross slope 1,71° dan lebar jalan tikungan 17 m. Dari batasan tersebut maka diperoleh batas penambangan seluas 8,3 Ha dengan metode penambangan yang akan digunakan yaitu metode side cast. Berdasarkan rancangan bukaan tambang, diperoleh cadangan tertambang sebesar 137,000 Ton nikel dengan kadar rata – rata 1,86 % dan 834,118 ton waste yang akan dikupas, menghasilkan stripping ratio 6,49 ton waste/ton ore dengan target produksi perusahaan sebesar 40,000 ton/bulan, sehingga penambangan akan direncanakan selama 3 bulan.